Metaphor and Senses : The Synamet Corpus: A Polish Resource for Synesthetic Metaphors - Zawisławska, Magdalena (2019)
The book deals with the synesthetic metaphors in Synamet – a semantically and grammatically annotated corpus. The texts included in the corpus are excerpted from blogs devoted to, among others, perfume, wine, beer, music, art, massage and wellness. The thesis presents a Conceptual Metaphor Theory (CMT) and frame-based analysis of synesthetic metaphors in Polish. Using data from the corpus, the book provides ample empirical support for embodiment in metaphor and internal logic of mappings between frames. The study proposes new models of verbal synesthesia in the corpus and calls into question a universality of hierarchy of senses. This book should be of interest to researchers working within cognitive linguistics, in particular metaphor theory, frame semantics, corpus linguistics, and sensory science.